Foetal and neonatal alloimune thrombocytopenia as a rare exapmle of thrombocytopenia in newborn - Maciej Kamiński; Paulina Grzesik; Monika Długoń; Maciej Majsterek; Żaneta Kimber-Trojnar; Krzysztof Kamiński; Bożena Leszczyńska-Gorzelak (Kazimierz Wielki University, 2018)
Foetal and neonatal alloimmune thrombocytopenia (FNAIT) is caused by antigenic incompatibility of platelets between a pregnant woman and her child, resulting in producing antibodies by a mother against specific antigens (HPA- Human Platelet Antigens) located on fetal platelets inherited from his father. The aim of this study is to present a 29-year-old patient in the 40th week of the second pregnancy admitted to the Department after rupturing of membranes. A male infant was born vaginally with numerous petechiae, bruising and yellowish skin colour. Due to severe thrombocytopenia 1 unit of leucocyte-reduced, irradiated, reconstituted platelet concentrate (LRIRPC) of blood group O RhD (+), suspended in plasma type AB was ordered. Human immunoglobulin (Kiovig preparation) was transfused. A check exam of complete blood count of the newborn revealed 5 x 103/µL of platelets count 4 hours after the transfusion. Following transfusions of LRIRPC and Kiovig were ordered. Again with no therapeutic effect. The newborn's HPA antigens were identified as: 1a/b; 2a/a; 3a/a; 5a/a; 4a/a; 15b/b, platelet antibodies derived from the mother were found in his serum. After transfusion of 1 unit of HPA-1b/b LRIRPC at 37 hours of the newborn's life the platelet count increased to 67 x103/µL. The treatment with dexamethasone and Kiovig was continued. The infant was discharged in good condition in the 33rd day of life. The FNAIT diagnostics is usually carried out only as a result of clinical manifestations of thrombocytopenia in the newborn. There was a possibility for all pregnant women from 8 weeks of pregnancy to have their blood tested for the presence of HPA-1a antigen in the period between October of 2013 to January of 2017 in Poland. It made it possible to nominate HPA-1a negative women.